Neo Sufisme dan Gerakan Sosial Agama-Politik di Madura - Hannan, Abd; Haryanto, Erie (Proceedings of Annual Conference for Muslim Scholars, 2019)
Madura society are identical with people who have religiosity, one form of their reigiosity is in the strong influence of religious symbols. In this context, religious groups such as the Madura ulama alliance (AUMA), is a contemporary Islamic movement that has significant influence, not only in terms of social religion, but also social politics. The study entitled, Neo Sufism and the Contemporary Social-Political Religion Movement in Madura. Some crucial issues discussed are; the concept of neo sufism from Fazlur Rahman, and Islamic religious-political social movements in Madura (AUMA). The two main issues above are then elaborated in two research questions; 1) What is the definition of neo sufism 2) How does the existence of AUMA, as a contemporary Islamic neo-Sufism movement, play a strategic role and function in the social dynamics of the religious-political community of Madura? This study is a field study based on qualitative research. The data in this paper were obtained through two sources, namely primary and secondary. he written findings contain an explanation of the existence of AUMA as a contemporary neo Sufism movement on Madura; the strategic role of AUMA's neo sufism in the social dynamics of the Madurese religious-political community. Generally, , this paper has made a major contribution in terms of explaining the dynamics and social discourse of the religious-political community of Madura, and the strategic role and function of the neo sufism religious group (AUMA) in the socio-political context of the local community